2021
DOI: 10.1016/j.amepre.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Academic Detailing to Increase Prescribing of HIV Pre-exposure Prophylaxis

Abstract: Although HIV pre-exposure prophylaxis can decrease new cases of HIV by up to 99%, many patients who could benefit from pre-exposure prophylaxis never receive prescriptions for it. Because pre-exposure prophylaxis is indicated for patients who do not have an infectious disease, increasing pre-exposure prophylaxis prescribing by primary care and generalist clinicians represents a key element of the Ending the HIV Epidemic in the U.S. initiative. This review provides an overview of academic detailing and how it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…First, our findings demonstrated prescribers who had a greater number of SUD clients were more likely to initiate PSS, suggesting these clinicians may have had greater awareness of announcements related to innovations in SUD care. Prescribers with smaller SUD client loads therefore may be harder to reach with passive dissemination strategies such as online educational materials and didactic lectures to learn about new clinical guidance and may require more active dissemination strategies such as academic detailing [ 24 , 25 ] or interactive educational meetings [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our findings demonstrated prescribers who had a greater number of SUD clients were more likely to initiate PSS, suggesting these clinicians may have had greater awareness of announcements related to innovations in SUD care. Prescribers with smaller SUD client loads therefore may be harder to reach with passive dissemination strategies such as online educational materials and didactic lectures to learn about new clinical guidance and may require more active dissemination strategies such as academic detailing [ 24 , 25 ] or interactive educational meetings [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNA can be used to pilot test the feasibility of an implementation [ 21 ]; design communication strategies [ 22 ] tailoring dissemination to opinion leaders, network isolates, and other prescribers with few clinical contacts; and evaluate implementation efforts [ 23 ]. Health administrative data can be used with SNA to model physicians’ social networks, creating opportunities to evaluate and inform the implementation and diffusion of new policies and interventions on a population level [ 24 , 25 ]. Previous research on diffusion of new policies has shown the influence of networks on tobacco regulations among countries [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests 43 that implicit bias can be changed with deliberate effort, at least in the short term. For instance, academic detailing 44 is one of the evidence-based outreach education strategies successfully used to support the scale-up of PrEP and target HIV and substance use–related biases. Considering the high burden of substance use disorders in the USA, it is critical to develop and implement effective strategies to prevent PCPs’ bias from negatively affecting clinical outcomes or contributing to health disparities among PWID.…”
Section: Discussionmentioning
confidence: 99%
“…Academic detailing 13 and practice facilitation 14 are other interactive and supportive implementation strategies that can assist with provision of substance use care 13 . Academic detailing is more focused on individual behavior change and uses a 1:1 strategy or small groups 13 ; thus, it may not be well suited for large-scale change such as implementing a new multidisciplinary service. Similar to TTA, practice facilitation addresses gaps, integrates care, increases adoption and acceptance, and builds capacity; however, practice facilitation includes formal goal setting and continuous improvement tools, which can be potentially more useful when growing or improving an existing intervention 14 .…”
Section: Other Approaches To Support Implementationmentioning
confidence: 99%
“…In addition, the individual support and building of a peer network likely would not have been matched by publicly available resources alone. Academic detailing 13 and practice facilitation 14 are other interactive and supportive implementation strategies that can assist with provision of substance use care 13 . Academic detailing is more focused on individual behavior change and uses a 1:1 strategy or small groups 13 ; thus, it may not be well suited for large-scale change such as implementing a new multidisciplinary service.…”
Section: Other Approaches To Support Implementationmentioning
confidence: 99%